1983
DOI: 10.1083/jcb.96.6.1631
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic microtubule assembly-disassembly from endogenous tubulin in a Brij-lysed cell model.

Abstract: We studied the characteristics of cytoplasmic microtubule reassembly from endogenous tubulin pools in situ using a Brij 58-1ysed 3T3 cell system. Cells that were pretreated in vivo with colcemid retain endogenous tubulin in the depolymerized state after lysis. When lysed cells were removed from colcemid block and incubated in GTP-PIPES reassembly buffer at pH 6.9, microtubules repolymerized randomly throughout the cytoplasm, appeared to be free-ended and were generally not associated with the centrosomes. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…It is known that the stability of microtubules and critical concentration for microtubule assembly are maximal at slightly acidic pH using purified brain and egg tubulin [Olmsted and Borisy, 1975;Regula et al, 1981;Suprenant, 1989;Simons et al, 1992;Tiwari and Suprenant, 1994]. Moreover, Deery and Brinkley [1983] reported that at a slightly acidified condition, microtubules assembled from endogeneous tubulin in the cell which was lysed and pretreated with colcemid. However, slightly alkaline pH, but not acidic pH, favored microtubule assembly in the crude extracts of eggs or oocytes [Suprenant and Marsh, 1987;Suprenant, 1989Suprenant, , 1991Simons et al, 1992;Tiwari and Suprenant, 1994].…”
Section: Discussionmentioning
confidence: 95%
“…It is known that the stability of microtubules and critical concentration for microtubule assembly are maximal at slightly acidic pH using purified brain and egg tubulin [Olmsted and Borisy, 1975;Regula et al, 1981;Suprenant, 1989;Simons et al, 1992;Tiwari and Suprenant, 1994]. Moreover, Deery and Brinkley [1983] reported that at a slightly acidified condition, microtubules assembled from endogeneous tubulin in the cell which was lysed and pretreated with colcemid. However, slightly alkaline pH, but not acidic pH, favored microtubule assembly in the crude extracts of eggs or oocytes [Suprenant and Marsh, 1987;Suprenant, 1989Suprenant, , 1991Simons et al, 1992;Tiwari and Suprenant, 1994].…”
Section: Discussionmentioning
confidence: 95%
“…In turn, this material amply justifies the term MTOC, since it was shown that such condensations not only seem to anchor the proximal ends of microtubules in certain cytoplasmic locations, but also act as sites for the initiation of microtubule assembly, which then proceeds by incorporating tubulin subunits preferentially at the distal ends [Inoué et al, 1974;Weisenberg and Rosenfeld, 1975;Brinkley et al, 1981;Deery and Brinkley, 1983;Mitchison and Kirschner, 1984;Soltys and Borisy, 1985;Rodionov et al, 1999]. Similarly, the basal bodies at the roots of cilia and flagella not only help to hold in place the proximal ends of the vibratile organelles, but also nucleate the assembly of tubulin upon themselves [Snell et al, 1974;Rosenbaum et al, 1975].…”
Section: Molecular Dynamics and Still More Websmentioning
confidence: 99%
“…The disagreement between these values has been considered in relation to the nucleation potential of microtubule organizing centers like centrosomes [6], suggesting that pH i regulates the nucleation potential of microtubule organizing centers [7,8]. Experiments have also shown that ionic concentrations play an important role in microtubule polymerization [9].…”
Section: Introductionmentioning
confidence: 99%